Patient-Derived Tumor Organoids: New Progress and Opportunities to Facilitate Precision Cancer Immunotherapy - Wang, Ji; Chen, Chao; Wang, Lu; Xie, Mingjun; Ge, Xinyang; Wu, Sufan; He, Yong; Mou, Xiaozhou; Ye, Chenyang; Sun, Yi (Frontiers in Oncology, 2022)
Cancer immunotherapy has revolutionized the field of cancer treatment in recent years. However, not all patients receiving cancer immunotherapy exhibit durable responses, and reliable, high-throughput testing platforms are urgently needed to guide personalized cancer immunotherapy. The ability of patient-derived tumor organoids to recapitulate pivotal features of original cancer tissues makes them useful as a preclinical model for cancer research and precision medicine. Nevertheless, many challenges exist in the translation of tumor organoid research to clinical decision making. Herein we discuss the applications of patient-derived tumor organoid models and the advances and potential of using complex immune-organoid systems as testing platforms to facilitate precision cancer immunotherapy. In addition, we highlight intriguing applications of tumor organoids with novel multi-omics in preclinical cancer research, highlighting genetic editing, proteomics, and liquid biopsy.